SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN RELAWAN TERBAIK DI PMI KOTA BENGKULU MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHT (SAW) - Samsuri Ridwan; Herlina Latipa Sari; Eko Suryana (Jurnal Media Infotama, 2015)
The main objectives and the holding of this study was to create a Decision Support System for Determining the Best Volunteer at PMI Bengkulu with Simple Additive Weighting method (SAW) using Visual Basic Programming Language 6.0. Data collection methods used in this study is the observation, interviews, and literature. Software used to build this system is the programming language Visual Basic 6.0 and the results obtained are able to provide fast and precise output. The results obtained from this study is a Decision Support System for Determining the Best Volunteer at PMI Bengkulu with Simple Additive Weighting method (SAW) which results in a decision that is the end result. From the main menu there is a system consisting of volunteers of data, weighting the data, the data value criteria, SPK and process data menu peorangan report that contains reports and ranking reports. From the discussion, it can be concluded that the Decision Support System for Determining the Best Volunteer at PMI Bengkulu Bengkulu Weigthing Simple Additive method (SAW) replaces the old system with a new system which is a program that is specific.Keywords: Decision Support System for Determining the Best Volunteer